A performance analysis of association rule mining algorithms - Fageeri, S.O. (Institute of Electrical and Electronics Engineers Inc., 2016)
In this paper, we evaluate the performance of association rule mining algorithms in-terms of execution times and memory usage using the CPU profiler of Java VisualVM. Mainly, and according to a previous work, we studied the performance of two main association rules algorithms which exhibits best results interms of execution time and memory usage: Binary-Based algorithm, and Eclat algorithm. The results of the CPU profiler of Java VisualVM showed that Binary-Based algorithm performs better than Eclat algorithm in-terms of both execution times and memory usage. In fact the results showed that Eclat algorithm sometimes even fails to produce any results and reports running out of memory exceptions. Â© 2016 IEEE.